Kaplan and Sadock's pocket handbook of Clinical Psychiatry - Sadock, B. J. Benjamin James (Wolters Kluwer, 2019)
Completely revised to bring you up to date with current DSM-5 classifications, new medications, and more, Kaplan & Sadock's Pocket Handbook of Clinical Psychiatry, Sixth Edition, is a concise, easy-to-use guide to diagnosing the full range of psychiatric disorders in both adults and children. Brief summaries of psychiatric disorders include key aspects of etiology, epidemiology, clinical features, and suggestions for treatment. It's an ideal ready reference for psychiatrists and other physicians, medical students on psychiatric rotations, psychiatric residents, and mental health professionals in psychology, social work, and nursing. Incorporates Diagnostic and Statistical Manual of Mental Disorders (DSM-5) into every chapter, ensuring that all diagnoses conform to DSM-5 classifications. Covers all aspects of psychological and pharmacological management. Concludes each chapter with specific page and chapter references to more detailed coverage in Kaplan and Sadock's Comprehensive Textbook of Psychiatry, Tenth Edition. Includes boxed, highlighted Clinical Hints for quick reference. Uses an easy-to-scan outline format throughout, making it a perfect source of quick review for busy clinical practitioners, psychiatric residents, or students preparing for exams.